Cloning and expression of hypothetical protein targets in burkholderia pseudomallei by Transposon-Directed Insertion Site Sequencing (TraDIS) technique - Drahaman, Siti Marhamah; Raih, Mohd Firdaus; Muhamad Bunnori, Noraslinda; Mohamed Rehan, Aisyah (Centre og Graduate Studies, Kolej Universiti Islam Selangor (KUIS), 2016)
Melioidosis is an infectious disease caused by a bacterium called Burkholderia pseudomallei found in contaminated water and soil. B. pseudomallei is naturally resistant to many commonly used antibiotics and thus current research efforts focus on prevention of disease and finding ways to reduce mortality. Identification of B. pseudomallei essential genes and its products may represent excellent targets for development of novel antimicrobial drugs. In this study, primers were designed for the PCR amplification of five target genes selected based on bioinformatics analysis from transposon-directed insertion site sequencing (TraDIS) library which compiles hypothetical proteins. Successfully amplified target genes were cloned into Gateway™ plasmid before being transformed into E. coli host. Expression trials of the target protein were performed for affinity tag protein purification. The presence of expressed soluble or non-soluble proteins were observed using SDS-PAGE electrophoresis. From this study, five selected target genes were successfully amplified using two-step PCR. One target gene, BPSL 2774 was successfully cloned into Gateway™ pDEST15 (GST-tagged) and purified using glutathione affinity protein purification kit. Mass spectrometry result has confirmed the presence of expressed and partially soluble GST-tagged protein of BPSL 2774. Using BLASTp search to PDB database and I-TASSER structure and function prediction softwares, BPSL 2774 is shown to have conserved domains of Glycosyltransferase GTB type superfamily and predicted to function as a glycosyltransferase. This enzyme is important in cell wall biosynthesis and transfer of sugar. This work provides the foundation for further investigation into the function of hypothetical protein BPSL2774, its possible role as a glycosyltransferase and as a potential virulence factor for B. pseudomallei.